Changing Patterns of Population Density in the Jammu and Kashmir - Javaid Ahmad Andrabi (Budapest International Research and Critics University, 2020)
The population growth and distribution has attracted increasing attention from geographers and planners in India from two or three decades to make the special approach in them to solve the human problems, which is a great task to handle. Here an attempt has been made on demographic dimensions of human resources to examine spatial and temporal variations in population growth and density during the last four decades (1981-2011). Density of population in the state is 124 persons per km2 (Census 2011). The study indicates that Srinagar and Jammu districts recorded high density of population of 2860 and 674 persons per km2 respectively, mainly on account of being the state’s administrative capitals which have made them the hub of socio-economic activities. The lowest population density is found in the Ladakh division with only 3 persons per km2 in Leh district. The population distribution and density pattern indicates an overwhelming influence of geo-physical disposition across the different regions of the Jammu and Kashmir state.